2014
DOI: 10.1007/s10096-014-2134-7
|View full text |Cite
|
Sign up to set email alerts
|

Co-infections with Borrelia species, Anaplasma phagocytophilum and Babesia spp. in patients with tick-borne encephalitis

Abstract: The purpose of this study was evaluation of the prevalence of co-infection with Borrelia species, A. phagocytophilum and Babesia spp. in patients with tick-borne encephalitis (TBE). At total of 110 patients with TBE were included in the study. Serological tests for tick-borne encephalitis virus (TBEV), PCR for Borrelia species, Anaplasma phagocytophilum and Babesia spp., blood smears for A. phagocytophilum and Babesia spp. and BLAST analysis for Babesia spp. were performed. Results showed a significant majorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 21 publications
7
42
0
4
Order By: Relevance
“…Analyses have been conducted following manufacturer's instructions: before June 2012 as a conventional PCR and after June 2012 in the nested type of PCR as previous described. [24] A positive control standard for A. phagocytophilum was included in the PCR Anaplasma diagnostic kit. [24] Presence of the 16S rRNA gene fragments in PCR-OUT (932 bp) and in PCR-IN (546 bp) attest to A. phagocytophilum infection.…”
Section: Pcr Amplificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyses have been conducted following manufacturer's instructions: before June 2012 as a conventional PCR and after June 2012 in the nested type of PCR as previous described. [24] A positive control standard for A. phagocytophilum was included in the PCR Anaplasma diagnostic kit. [24] Presence of the 16S rRNA gene fragments in PCR-OUT (932 bp) and in PCR-IN (546 bp) attest to A. phagocytophilum infection.…”
Section: Pcr Amplificationsmentioning
confidence: 99%
“…[24] A positive control standard for A. phagocytophilum was included in the PCR Anaplasma diagnostic kit. [24] Presence of the 16S rRNA gene fragments in PCR-OUT (932 bp) and in PCR-IN (546 bp) attest to A. phagocytophilum infection. Lack of 932 bp long fragments in PCR-OUT did not exclude a positive result of test.…”
Section: Pcr Amplificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Do zarażenia dochodzi najczęściej wskutek ukłucia przez zakażonego kleszcza, ale też drogą krwiopochodną. Opisane, wykryte na terenie Polski, przypadki zostały zawleczone z krajów tropikalnych i stwierdzono je u pacjentów ze współistniejącymi innymi TBD lub odkryto w ramach badań naukowych [59]. Tymczasem, jak wykazały zespoły badawcze Chmielewskiej-Badory i wsp.…”
Section: Ludzka Anaplazmoza Granulocytarnaunclassified
“…In 2007, Grab et al found that the infection of A. phagocytophilum may be responsible of a more severe form of LD with enhanced dissemination and possible long-term complications because co-infection causes reduction in transendothelial electric resistance and increased production of metalloproteinases, cytokines and chemokines [20,21].…”
Section: Anaplasma Phagocytophilummentioning
confidence: 99%